Use of curable and re-separable composition for manufacture of component and composition therefor
By using a curable composition containing an epoxy compound and a polymer filler, combined with a solidification technology of actinic radiation or a thermal initiator, the problem of insufficient bonding strength and durability of the joints under high thermal load conditions in the prior art is solved, and efficient re-removal of the adhesive layer is achieved.
Patent Information
- Application Number
- CN202380057924.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-07-19
- Publication Date
- 2025-03-18
AI Technical Summary
Removable compositions for joints in the prior art are difficult to maintain bond strength and durability under high thermal load conditions and require a large amount of energy consumption or a harsh process during disassembly.
The composition is solidified by actinic radiation or thermal initiator and re-removal of the adhesive layer is achieved at a predetermined temperature using a curable composition comprising an epoxy compound, a nitrogen-based curing agent, a polymer filler and a radical polymerization cured compound.
Maintain high bond strength and durability under high thermal load conditions while achieving re-removal of the adhesive layer at lower energy input, avoiding damage to the service life of the machine.
Smart Images

Figure CN119654376A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the use of a curable composition for producing a component having a thermomechanically removable joint, coating or casting, and to a curable composition for producing the component. The curable composition comprises at least an epoxy compound, a curing agent for the epoxy compound and a polymer filler.
[0002] The invention furthermore relates to a method for producing a component having a thermomechanically removable joint, coating or casting using the curable composition, and to a component obtainable by this method. Background Art
[0003] The circular economy aims to establish a system in which resource utilization and waste generation are minimized, for example by closing energy and material cycles. From this perspective, the reuse of components or parts in industry is a major challenge. In particular, in the case of high-value or limited global supply parts that age relatively little during long-term use, there is a strong desire to be able to use them directly or in recycled form in new products. However, these parts are often located in complex devices that must be disassembled before they can be separated from other components. In the context of the circular economy, it is desirable to consume as little energy as possible during the disassembly process and to avoid the use of harsh processes such as pyrolysis. In addition, from an ecological point of view, solvents should not be used during the disassembly process. Therefore, there is a need in the prior art for compositions that enable the re-removal of joined parts with an acceptable energy input and under conditions that are as gentle as possible. At the same time, the composition must not shorten the service life of the machine during operation or impair its performance.
[0004] In the prior art, there are a variety of methods to make the joints removable. Usually, heat is input through mechanical force to separate the joint parts from each other in a thermomechanical manner. Other methods include using solvents and pyrolyzing, exposing or applying electricity to the joints.
[0005] EP 1 096 517 A2 discloses a recovery method for producing magnetic powder from joined magnets. The joined parts contain thermoplastic materials which are separated under harsh conditions by means of solvents.
[0006] WO 1998 031 738 A1 describes an epoxy-amine composition comprising a modified amine curing agent, which composition additionally comprises a plasticizer. The composition is intended for bonding and repairing semiconductor components. The repair process involves softening the cured composition by treating with hot air at 250° C. for 1 minute.
[0007] JP 3 808 819 B2 describes a method for recovering joined magnets by treating them with hot water and then stripping them off. The adhesive used to hold the magnets in place also contains organic heat-expanding particles that expand when exposed to hot water at 70°C-120°C. Such compositions are not suitable for magnets used, for example, in powerful electric motors, since the prescribed removal temperature is often reached or exceeded even during normal operation.
[0008] US Pat. No. 5,872,158 A describes removable compositions based on (meth)acrylates which comprise acetal-functionalized diacrylates. This publication provides for the separation of the cured compositions by treatment with dilute acid and cleavage of the acetal groups.
[0009] US2007 0 196 612A1 describes a chip attachment composition based on epoxide, (partial) fluorinated aromatic amine curing agent, inorganic filler and organic additive. Organic additives include polyacrylates, butadiene-styrene copolymers, polyamides and EVA copolymers. Organic additives exceeding 20wt% are not included because this will unfavorably increase the viscosity of the composition. In order to separate the silicon chip from the cured composition, it is treated with a mixture of solvents (e.g., N, N-dimethylformamide or bis(2-methoxyethyl) ether). This approach is problematic in ecotoxicology and may also cause adverse damage to surrounding components.
[0010] WO 2021 033 368A1 discloses an epoxyamine composition, which further comprises a polymer component and at least one inorganic filler. The polymer component comprises at least one phenoloxy resin, which is present in the form of being dissolved in the composition. In order to consider the re-removal of the joined parts.
[0011] EP 2 084 205 B1 describes a fiber-reinforced composite material comprising at least one difunctional epoxy resin and an additional trifunctional epoxy resin. As a curing agent, it is recommended to use a nitrogen-based compound. In addition, insoluble particles from polyamides are added to the composition. These improve the so-called CAI value (compression after impact), thereby improving the mechanical recovery properties of the cured composition. The removability of the composition is not described. On the contrary, these compositions are described as a matrix for the production of prepregs in the aerospace industry.
[0012] The compositions described in the prior art either require very harsh conditions for separation or are not suitable for permanent use as joining materials in machines which are already subject to high thermal loads during normal operation. Summary of the invention
[0013] The object of the present invention is to avoid the above-mentioned disadvantages of the compositions known from the prior art.
[0014] In particular, the aim is to provide compositions which are removable and which retain their high bond strength and durability over the life cycle of the device or component in which they are used, even under thermal load or exposure to media.
[0015] According to the present invention, the above objects are achieved by the use of the curable composition according to claim 1, the curable composition according to claim 8, the method for producing a component using the composition according to claim 9, and the component obtainable by the method according to claim 10.
[0016] Advantageous embodiments according to the invention are given in the dependent claims which can optionally be combined with one another.
[0017] According to the invention, a curable composition for producing a component having a thermomechanically removable joint, coating or casting comprises the following components:
[0018] (a) at least one epoxy compound, the epoxy compound comprising at least one difunctional or higher functional aromatic epoxide;
[0019] (b) at least one curing agent suitable for epoxy curing, preferably a nitrogen-based curing agent;
[0020] (c) optionally an accelerator for epoxy curing;
[0021] (d) at least one polymer filler, the polymer filler being present in an amount of 15 wt% or more based on the total weight of the composition, wherein the polymer filler is selected from the group of polyamides;
[0022] (e) optionally one or more compounds curable by free radical polymerization;
[0023] (f) optionally at least one initiator for free radical polymerization; and
[0024] (g) optionally other additives,
[0025] The polymeric filler is present in the composition as an at least partially crystalline solid, wherein the polymeric filler has a melting point of at least 120°C.
[0026] The component preferably has a joint. In particular, the composition according to the invention is suitable for bonding magnets, in particular for producing stators and / or rotors of electric motors.
[0027] According to an embodiment, the curable composition according to the present invention comprises the following components:
[0028] (a) at least one epoxy compound, the epoxy compound comprising at least one difunctional or higher functional aromatic epoxide;
[0029] (b) at least one nitrogen-based curing agent suitable for epoxy curing;
[0030] (c) optionally an accelerator for epoxy curing;
[0031] (d) at least one polymer filler, the polymer filler being present in an amount of 20 wt% or more based on the total weight of the composition, wherein the polymer filler is selected from the group consisting of polyamides;
[0032] (e) optionally one or more free radical radiation curable compounds;
[0033] (f) optionally at least one initiator for free radical polymerization; and
[0034] (g) optionally other additives,
[0035] In this embodiment, the polymeric filler is present in the composition as an at least partially crystalline solid, the polymeric filler having a heat of fusion of 40 J / g or more, preferably 50 J / g or more. The polymeric filler has a melting point of at least 120°C.
[0036] The composition according to the invention is characterized by being removable at a predetermined temperature, at which a significant drop in modulus and a correspondingly high loss of strength can be observed in the storage modulus DMTA curve of the cured composition. At the same time, the cured composition has a high degree of crosslinking and a high glass transition temperature. This ensures a minimal drop in strength under thermal load and good media resistance.
[0037] According to another aspect, the present invention relates to a method for manufacturing a component using the curable composition described above, wherein the method comprises the following steps:
[0038] a) applying the composition to a first substrate in a quantitative manner;
[0039] b) optionally, providing a second substrate to form a substrate composite, wherein the second substrate is contacted with the composition;
[0040] c) optionally, irradiating the composition with actinic radiation, thereby providing the irradiated composition with a sufficient anchor strength for further processing of the first substrate or substrate composite; and
[0041] d) heating the optionally irradiated composition on the substrate or substrate composite to a predetermined curing temperature until it is cured, thereby forming a component having the substrate and a cured adhesive layer connected to the substrate or optionally to another substrate, wherein the cured adhesive layer can be thermomechanically separated from the substrate by heating to at least one removal temperature.
[0042] Preferably, the component comprises a substrate composite in which at least two substrates are connected via an adhesive layer.
[0043] The storage modulus (E') of the cured composition, measured by dynamic mechanical thermal analysis (DMTA) versus temperature, has at least one further inflection point in the curve above the glass transition temperature.
[0044] The other inflection point is located in a temperature range in which a sharp and significant decrease in the storage modulus and the strength of the cured composition can be observed. Preferably, the difference between the end and the starting point of the temperature range including the other inflection point (i.e., between the end and the starting point of the modulus decrease) does not exceed 30°C, more preferably does not exceed 20°C or 15°C. Particularly preferably, in the DMTA curve, the modulus decrease occurs in a temperature interval of 10°C or less. The absolute temperature of the other inflection point in the DMTA curve can be adjusted by selecting a partially crystalline polymer filler.
[0045] Preferably, the removal temperature, at which the adhesive layer can be thermomechanically separated from the substrate or substrate composite, is selected to be located at or above another inflection point in the DMTA curve of the storage modulus of the cured composition. More preferably, the removal temperature is in the range between the temperature of the other inflection point and at most 50°C, more preferably at most 20°C above the end point of the modulus drop. It goes without saying to a person skilled in the art that the adhesive layer can also be removed at higher temperatures. However, the closer the removal temperature is to the end point of the modulus drop, the more energy-efficient and efficient the recovery of the valuable substrate is.
[0046] In a preferred embodiment, the removal temperature does not exceed 320° C., more preferably does not exceed 280° C., particularly preferably does not exceed 250° C. At higher temperatures, there may be a risk of thermal damage to the components to be recycled. In addition, such high temperatures offer little energy advantage compared to pyrolysis.
[0047] Another object of the present invention is to provide a component having a releasable adhesive layer, which component is obtainable by the above method. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In the figure it is shown:
[0049] Figure 1DMTA curves are shown, in which the storage modulus of a reference composition and of a composition used according to the invention is indicated as a function of temperature. DETAILED DESCRIPTION
[0050] The present invention will be described in detail below by way of examples with reference to preferred embodiments, but these preferred embodiments should not be construed as limitative.
[0051] "Liquid" within the meaning of the present invention means that at 23° C. the loss modulus G″ determined by viscosity measurement is greater than the storage modulus G′ of the component in question.
[0052] Generally, when using the indefinite article "a / an (ein / eine)", it includes its plural form "one / a kind or more / a kind" unless expressly excluded.
[0053] "At least difunctional" means units which contain two or more of the functional groups mentioned per molecule. No distinction is made here between primary, secondary and tertiary functional groups.
[0054] Unless otherwise indicated, all weight ratios listed below refer to the total weight of all components.
[0055] The composition according to the present invention can be formulated as either a one-component type or a multi-component type.
[0056] Component (a): Epoxy compound
[0057] The chemical structure of the epoxy compound (a) is not further restricted and comprises at least one difunctional or higher-functional aromatic epoxide. The use of aromatic epoxy compounds can produce compositions with high glass transition temperatures, which remain mechanically stable under thermal load and have good media resistance.
[0058] Preferably, aromatic glycidyl ethers, glycidyl esters, glycidyl amines and mixtures thereof are used.In addition, aliphatic and cycloaliphatic epoxy compounds or monofunctional epoxy compounds can also be contained in component (a) as reactive diluents.
[0059] Aromatic glycidyl ethers are obtained by reacting epichlorohydrin with aromatic alcohols and phenols. Examples of such aromatic epoxy compounds and their respective trade names are bisphenol A epoxy resin (DER331, Epikote Resin 828), bisphenol F epoxy resin (Epikote Resin 862, Epikote Resin 863, YDF-170), a mixture of bisphenol A and F diglycidyl ether (DER351, Epikote Resin 166, YDF-161), phenol novolac epoxy resin (DEN424, DEN437, DEN440, YDPN-631), and cresol novolac epoxy resin (DIC Corporation Epiclon N-670, YDCN-500-5P).
[0060] Furthermore, glycidyl ethers based on aromatic phenols, such as 1,6-naphthalene diol (Araldite MY0816), tris(hydroxyphenyl)methane (Tactix 742), various bisphenols, hydroxy-substituted biphenyls (e.g. jER YX4000H) or monofunctional glycidyl ethers, for example based on p-tert-butylphenol (DER727) or cardanol (Cardolite Lite513), can also be used.
[0061] In addition, diglycidyl ethers based on aliphatic alcohols can be used, such as butanediol (Araldite DY-D), hexanediol (Araldite DY-H), cyclohexanedimethanol (Araldite DY-C), polymer diols (such as polyoxypropylene glycol, Araldite DY-F), dicyclopentadiene dimethanol (Adeka EP 4088S). In addition, reaction products of epichlorohydrin with amines or aminophenols can be used, such as TGAP (triglycidyl ether of aminophenol; Araldite MY 0610) or TGMDA (methylenedianiline tetraglycidyl; Araldite MY 721).
[0062] All fully or partially hydrogenated aromatic epoxy analogs may also be used. Preferred are hydrogenated bisphenol A and bisphenol F epoxy resins (eg Eponex Resin 1510).
[0063] In addition, aromatic compounds (such as terephthalic acid ( PT 910, Fa. Huntsman)), glycidyl esters of cycloaliphatic compounds or aliphatic compounds (Cardura E10, Fa. Westlake).
[0064] In addition to the epoxy compounds described above, cycloaliphatic epoxides may also be used in the compositions according to the invention. Suitable examples are 3-cyclohexenylmethyl-3-cyclohexylcarboxylic acid diepoxide, 3,4-epoxycyclohexylalkyl-3',4'-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3',4'-epoxy-6-methylcyclohexanecarboxylate, vinylcyclohexene dioxide, bis(3,4-epoxycyclohexylmethyl)adipate, dicyclopentadiene dioxide, dicyclopentadieneoxyethyl glycidyl ether, limonene dioxide and 1,2-epoxy-6-(2,3-epoxypropoxy)hexahydro-4,7-methaneindane and mixtures thereof.
[0065] Furthermore, epoxides based on fats / oils can be used, for example Sovermol 1055, BASF.
[0066] Isocyanurates and other heterocyclic compounds substituted with epoxy groups can also be used as component (a) in the composition according to the invention, for example triglycidyl isocyanurate and monoallyl diglycidyl isocyanurate.
[0067] Furthermore, it is also possible to use monofunctional and polyfunctional epoxy resins from all of the abovementioned resin groups which, in addition to the epoxy function, also contain further functional groups, for example, oligomeric aromatic epoxy compounds with OH functions (for example Dow DER 671 or Kukdo KD-9004).
[0068] It is also possible to use addition products of the above-mentioned epoxy compounds with H acidic compounds (in low molecular weight or polymer form) such as carboxylic acids, alcohols and / or thiols. Particularly preferably, examples are addition products of reactive liquid rubbers, such as epoxy compounds with CTBN rubber (e.g. Albipox 2000) or dimerized fatty acids (e.g. B-Tough A1).
[0069] Also within the meaning of the present invention are combinations of a plurality of epoxy-containing compounds, at least one of which is difunctional or higher-functional.
[0070] In addition to all the abovementioned epoxy-containing compounds, sulfur analogs can also be used as component (a). The corresponding thiirane is also included in the meaning of the present invention. It is also possible to advantageously use epoxides in which some of the epoxy groups are replaced by thiirane.
[0071] In the composition according to the present invention, component (a) is preferably present in a proportion of 10 wt% to 80 wt%, more preferably 20 wt% to 70 wt%, based on the total weight of the composition.
[0072] In the component (a), the monofunctional epoxy compound may be present in a proportion of up to 30% based on the total weight of the component (a).
[0073] Component (b): Curing agent for epoxy compound
[0074] The composition according to the invention comprises at least one curing agent (b) for epoxy curing. The chemical structure of component (b) is not further limited; preferably comprises a nitrogen-based curing agent; more preferably comprises a curing agent selected from the group of primary, secondary, and tertiary amines, cyanamides, imidazoles, hydrazides and / or epoxy adducts of the above compounds. Preferably, in the composition, the curing agent is present in solid form.
[0075] Commercial examples of suitable solid amine curing agents containing primary, secondary and / or tertiary amine groups are Ancamine 2014AS (Evonik), Ancamine 2337S (Evonik), Ajicure PN-23J (Ajinomoto), Aradur 9506 (Huntsman), FUJICURE FXR-1121 (Sanho), FUJICURE FXR-1020 (Sanho), Hardener XB 3123 (Huntsman), Versalink 740M (Evonik), Lonzacure M-CDEA, Primacure M-DEA, Aradur 9664-1 (Huntsman) and Aradur 9719-1 (Huntsman). The curing agent preferably contains at least two nitrogen-containing groups per molecule suitable for epoxy curing.
[0076] Commercial examples of suitable curing agents from the group of cyanamides are Dyhard 100SF from Alzchem, DICYANEX 1200 from Evonik and EPIKURE Curing Agent P-104 from Westlake.
[0077] Commercial examples of suitable solid imidazole curing agents are Adeka Hardener EH-5011S, AdekaHardener EH-5046S, Technicure LC-80 (ACCI Specialty Materials), and Curezol 2P4MZ (Shikoku).
[0078] Commercial examples of suitable hydrazides are Technicure ADH-J (ACCI Specialty Materials), Technicure IDH-J (ACCI Specialty Materials), Ajicure UDH-J (Ajinomoto), and Ajicure VDH-J (Ajinomoto).
[0079] By combining different curing agents (b), epoxy curing can be accelerated without adding component (c). Commercial examples of nitrogen-containing compounds that have an accelerating effect on curing, especially when combined with another curing agent (b), are Ancamine 2014AS (Evonik), Ancamine 2337S (Evonik), Ajicure PN-23J (Ajinomoto), Aradur 9506 (Huntsman), FUJICURE FXR-1121 (Sanho), FUJICURE FXR-1020 (Sanho), Hardener XB 3123 (Huntsman), Adeka Hardener EH-5011S, Adeka Hardener EH-5046S and Technicure LC-80 (ACCI Specialty Materials).
[0080] In the case of two-component or multi-component compositions, liquid amines from the group of aliphatic or cycloaliphatic amines, polyetheramines, polyamides, Mannich bases, or reaction products thereof with epoxy resins and combinations thereof are particularly suitable as component (b). These amines exhibit a high reactivity even at room temperature and cure component (a) without additional heating after mixing. Specific examples of suitable amines can be found in DE 10 2018 121 067 A1.
[0081] The above list is only exemplary and not exhaustive. Mixtures of the curing agent (b) are also within the meaning of the present invention.
[0082] As the curing agent (b) for epoxy curing, acid anhydrides and mercaptans can also be used.
[0083] Specific examples of the acid anhydride that can be used as the curing agent for the epoxide in the composition include anhydrides of dibasic acids such as phthalic anhydride (PSA), succinic anhydride, octenyl succinic anhydride (OSA), pentadecenyl succinic anhydride and other alkenyl succinic anhydrides, maleic anhydride (MA), itaconic anhydride (ISA), tetrahydrophthalic anhydride (THPA), hexahydrophthalic anhydride (HHPA), methyltetrahydrophthalic anhydride (MTHPA) , methylhexahydrophthalic anhydride (MHHPA), nadic anhydride, 3,6-endomethylenetetrahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride (METH, NMA), tetrabromophthalic anhydride and trimellitic anhydride; and anhydrides of aromatic tetrabasic acids, such as biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, biphenyl ether tetracarboxylic dianhydride, butanetetracarboxylic dianhydride, cyclopentanetetracarboxylic dianhydride, pyromellitic anhydride and benzophenonetetracarboxylic dianhydride. The compounds can be used alone or in combination of two or more thereof.
[0084] Among these acid anhydrides, preferably compounds which are liquid at room temperature are used as the curing agent (b), such as methylhexahydrophthalic anhydride (MHHPA), methyltetrahydrophthalic anhydride (MTHPA), methylendomethylenetetrahydrophthalic anhydride (METH, NMA) and hydrogenated products thereof.
[0085] Preferably, the acid anhydride used as the curing agent (b) is commercially available, for example, under the following trade names: MHHPA, for example, under the trade names HN-5500 (Hitachi Chemical Co., Ltd.) and MHHPA (Dixie Chemical Company, Inc.); METH, under the trade names NMA (Dixie Chemical Company, Inc.), METH / ES (Polynt SpA) and MHAC (Hitachi Chemical Co., Ltd.).
[0086] When a thiol-based epoxy curing agent (b) is used, the curing agent includes at least one compound having at least two thiol groups (-SH) in the molecule. The chemical structure of the thiol is not further limited, and preferably includes aromatic thiols and aliphatic thiols and combinations thereof.
[0087] Preferably, the at least bifunctional thiol is selected from the group consisting of ester thiols, polyethers having reactive thiol groups, polythioethers, polythioether acetals, polythioether thioacetals, polysulfides, thiol-terminated polyurethanes, glycolurils and thiol derivatives of isocyanurates, and combinations thereof.
[0088] Examples of commercially available 2-thioglycolic acid-based ester mercaptans include trimethylolpropane trimercaptoacetate, pentaerythritol tetramercaptoacetate, and ethylene glycol dimercaptoacetate, which are available under the trade name Thiocure TM TMPMA, PETMA and GDMA were purchased from Bruno Bock.
[0089] Other commercially available examples of ester mercaptans include trimethylolpropane-tris(3-mercaptopropionate), pentaerythritol-tetrakis(3-mercaptobutyrate), ethylene glycol-di(3-mercaptopropionate), and tris[2-(3-mercaptopropionyloxy)ethyl]isocyanurate, which are available from Bruno Bock under the trade names Thiocure TMPMP, PETMP, GDMP, and TEMPIC.
[0090] Examples of commercially available thioethers include DMDO (1,8-dimercapto-3,6-dioxaoctane), available from Arkema S.A.; DMDS (dimercaptodiethyl sulfide) and DMPT (2,3-bis((2-mercaptoethyl)thio)-1-propane-thiol), both available from Bruno Bock.
[0091] With regard to increasing the resistance of the cured composition to temperature and humidity, the use of ester-free thiols is particularly preferred. Examples of ester-free thiols can be found in JP 2012 153 794A.
[0092] Particularly preferably, tris(3-mercaptopropyl)isocyanurate (TMPI) is used as trifunctional, ester-free thiol.
[0093] Ester-free thiols based on glycoluril compounds are already known from EP 3 075 736 A1. The thiols can also be used as curing agents (b) alone or in a mixture with other at least difunctional thiols.
[0094] It is also possible to use higher-functional thiols, obtained, for example, by oxidative dimerization of at least difunctional thiols.
[0095] The above list is merely illustrative and not exhaustive.
[0096] In the composition according to the present invention, the proportion of the curing agent (b) is preferably 1 wt % to 50 wt %, more preferably 2 wt % to 30 wt %.
[0097] Component (c): Accelerator
[0098] In the composition according to the invention, at least one accelerator (c) may optionally be used for epoxy curing. For example, the accelerator is selected from the group of urea derivatives, amines and imidazoles.
[0099] Examples of suitable accelerators based on urea and its derivatives are uretones. Commercially available examples include Dyhard UR500 (Alzchem), Dyhard UR 300 (Alzchem), EPICURE Catalyst 116 (Westlake), Technicure MDU-11M (ACCI Specialty Materials), Technicure IPDU-8 (ACCI Specialty Materials), Technicure MDU-11M (ACCI Specialty Materials), Dyhard UR 800 (Alzchem), URAcc 57 (Alzchem), UR 700 (Alzchem), UR 500 (Alzchem), EPICURE Catalyst 116 (Westlake).
[0100] Examples of suitable accelerators based on amines are Ancamine 2014AS (Evonik), Ancamine 2337S (Evonik), Ajicure PN-23J (Ajinomoto), Aradur 9506 (Huntsman), FUJICURE FXR-1121 (Sanho), FUJICURE FXR-1020 (Sanho).
[0101] Examples of suitable accelerators based on imidazole are Adeka Hardener EH-5011S, Adeka Hardener EH-5046S, Technicure LC-80 (ACCI Specialty Materials), Curezol 2P4MZ (Shikoku).
[0102] The accelerators (c) listed here are to be understood explicitly as compounds with additional accelerator effects not included in the combination (b) and combinations thereof. The use of a plurality of accelerators also lies within the meaning of the present invention.
[0103] In the composition of the present invention, the accelerator (c) is preferably present in a proportion of 0 wt % to 5 wt %, more preferably in a proportion of 1 wt % to 3 wt %, based on the total weight of the composition.
[0104] Component (d): polymer filler
[0105] The composition according to the present invention comprises at least one organic polymer filler (d). The filler is selected from the group consisting of polyamides and has a melting point of at least 120° C. In the composition, the polymer filler is present as an at least partially crystalline solid, and the proportion of the filler in the composition is 15 wt % or more, based on the total weight of the composition. A lower proportion of semi-crystalline polymer fillers may result in insufficient removability of the cured composition at a predetermined removal temperature. Adhesive layers made from these compositions can only be removed from the corresponding substrates by greater force.
[0106] Preferably, the organic filler is selected from the group of polyamide 6, polyamide 6.6, polyamide 11, polyamide 12 and copolymers thereof.
[0107] The melting point of filler (d) is preferably higher than 120° C., and preferably at least 140° C., more preferably at least 160° C. The melting point of component (d) is preferably lower than 300° C., more preferably lower than 250° C. The melting point refers to the peak temperature of the polymer filler or the cured composition containing the filler measured in a DSC analysis carried out at a heating rate of 10 K / min.
[0108] More preferably, the median particle size D50 of the polymer filler (d) is less than 100 μm, more preferably less than 50 μm, as can be determined by laser diffraction.
[0109] Examples of commercially available polymeric fillers include: Rilsan series D20, D30, D40, D50, D60, D80, Orgasol 2001, Orgasol 2002, Orgasol 1002 and Orgasol 3501, available from Arkema, and Ultrasint PA6 and Ultrasint PA11 from BASF. For example, commercially available particles (e.g., Ertalon 6PLA and Ertalon 66SA from Mitsubishi Chemical Advanced Materials, or Zytel 7335F NC010 from DuPont) can be converted to a suitable particle size distribution by mechanical grinding.
[0110] The choice of component (d) depends on the intended application context of the cured composition. Preferably, the melting point of the filler (d) is selected to be at least 5°C, preferably at least 10°C higher than the average temperature to which the cured composition is permanently exposed in its application. In the sense of energy saving for re-removal, preferably, the temperature difference between the starting point of the modulus drop in the DMTA curve of the storage modulus and the application temperature of the composition below the starting point is small. In applications where temperature peaks may occur more frequently, a higher temperature difference is preferred for reliability reasons.
[0111] The heat of fusion of the polymeric filler (d) used in the composition according to the invention is at least 40 J / g, preferably 50 J / g. The heat of fusion indicates the degree of crystallinity of the filler (d) used.
[0112] In the composition of the present invention, the proportion of the at least partially crystalline polymer filler (d) is at least 15 wt %, preferably at least 20 wt % or 25 wt %, but at most 50 wt %, based on the total weight of the composition. A higher proportion of the at least partially crystalline polymer filler may result in a liquid curable composition having a high viscosity that is not conducive to processing, and in the cured composition having insufficient temperature resistance or media resistance.
[0113] Component (e): Free radical curable compound
[0114] The composition optionally comprises a compound (e) curable by free radical polymerization, said compound (e) comprising at least one (meth)acrylate. Within the meaning of the present invention, "(meth)acrylate" includes both acrylate and its analog methacrylate. The use of component (e) can allow rapid solidification of the composition, in particular by irradiation with actinic radiation.
[0115] The (meth)acrylate of component (e) is not further limited in structure, and includes, for example, linear, branched, aliphatic, aromatic and heterocyclic (meth)acrylates, and combinations thereof.
[0116] Within the meaning of the present invention, (meth)acrylates are also monomeric, oligomeric or polymeric compounds, provided that they comprise at least one (meth)acrylate group which is crosslinkable by free radicals.
[0117] Preference is given to (meth)acrylates whose homopolymers have a glass transition temperature of more than 100° C. but at the same time below the removal temperature of the cured composition of the invention.
[0118] Preferably, the composition comprises at least one difunctional or polyfunctional (meth)acrylate.
[0119] Examples of difunctional or polyfunctional (meth)acrylates are hexanediol di(meth)acrylate, di(trimethylolpropane) tetraacrylate, 4-butanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, cyclohexane dimethylol di(meth)acrylate, nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tri-(2-hydroxyethyl)isocyanuric acid tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, dipentaerythritol hexa(meth)acrylate, BPA-dipropylene oxide di(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate.
[0120] Such (meth)acrylates are commercially available from companies such as Arkema Sartomer, BASF, IGM Resins, Sigma Aldrich or TCI.
[0121] Besides difunctional or polyfunctional (meth)acrylates, it is also possible to use monofunctional aliphatic, cycloaliphatic or aromatic (meth)acrylates.
[0122] Examples of suitable monofunctional (meth)acrylates include isobornyl (meth)acrylate, cyclic trimethylolpropanecarboxyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, tert-butylcyclohexanol methacrylate, and octahydro-4,7-methyl-1H-indenyl methyl (meth)acrylate.
[0123] (Meth)acrylates with a low solubility relative to the curing agent (b) are preferred. This gives the composition an advantageous latency at room temperature.
[0124] Furthermore, it is also possible to use mixed compounds which, in addition to the radiation-curable groups, also contain addition-crosslinkable groups. Examples of compounds which, in addition to (meth)acrylate groups, also have epoxy groups are so-called epoxy acrylates, such as Solmer SE 1605 available from Soltech Ltd, Cyclomer M100 available from Daicel, RCX 14-786 from Rahn AG, and 4-hydroxybutyl acrylate monoglycidyl ether available from Mitsubishi Chemical Europe GmbH.
[0125] The above-mentioned list of applicable material categories is merely exemplary and should not be construed as limiting.
[0126] In the composition of the present invention, the proportion of component (e) is 0 wt % to 40 wt %, preferably 1 wt % to 30 wt %, based on the total weight of the composition.
[0127] In component (e), the proportion of the difunctional or polyfunctional (meth)acrylate is preferably at least 50%, more preferably at least 60%.
[0128] Component (f): Initiator for free radical polymerization
[0129] For curing component (e), the composition according to the invention optionally comprises at least one initiator (f) for free radical polymerization. Photoinitiator (f1) in combination with component (e) can solidify the composition by irradiation with actinic radiation. Thermal initiators (f2) for free radical polymerization thermally cure compound (e). In photocurable formulations, in addition to photoinitiator (f1), initiator (f2) can advantageously be used to achieve complete curing of areas of the curable composition that are inaccessible to actinic radiation.
[0130] As the free radical photoinitiator (f1), common commercially available compounds can be used, for example, α-hydroxyketone, benzophenone, α,α'-diethoxyacetophenone, 2-benzyl-2-(dimethylamino)-4'-morpholinobutyl ketone benzene, 4-isopropylphenyl-2-hydroxy-2-propyl ketone, 4,4-bis(diethylamino)benzophenone, 2-ethylhexyl-4-(dimethylamino)benzoate, ethyl 4-(dimethylamino)benzoate, 2-butoxyethyl-4-(dimethylamino)benzoate, 1-hydroxycyclohexyl phenyl ketone, p-dimethyl Isoamyl aminobenzoate, methyl 4-dimethylaminobenzoate, methyl o-benzoylbenzoate, benzoin, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-isopropylthioxanthone, dibenzosuberone, ethyl-(3-benzoyl-2,4,6-trimethylbenzoyl)(phenyl)phosphonate, methyl benzoylformate, oxime ester, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate and bisacylphosphine oxide.
[0131] Preferably, the free radical photoinitiator (f1) can be activated by irradiation with actinic radiation having a wavelength of 200 nm to 600 nm, particularly preferably 320 nm to 480 nm. If necessary, the free radical photoinitiator can be combined with a suitable sensitizer.
[0132] Commercially available photoinitiators that can be used include, for example, IRGACURE® from BASF SE. TMSeries, such as IRGACURE 184, IRGACURE 500, IRGACURE 1179, IRGACURE 2959, IRGACURE 745, IRGACURE651, IRGACURE 369, IRGACURE 907, IRGACURE 1300, IRGACURE 819, IRGACURE 819DW, IRGACURE 2022, IRGACURE 2100, IRGACURE 784, IRGACURE 250, IRGACURE TPO, IRGACURE TPO-L. You can also use BASF SE’s DAROCUR TM series, such as DAROCUR MBF, DAROCUR 1173, DAROCUR TPO and DAROCUR 4265.
[0133] The above-mentioned list of applicable material categories is merely exemplary and should not be construed as limiting.
[0134] Combinations of multiple photoinitiators are also contemplated by the present invention.
[0135] In the composition of the present invention, the proportion of the free radical photoinitiator (f1) is preferably 0 wt % to 5 wt %, more preferably 0.1 wt % to 3 wt %, based on the total weight of the composition.
[0136] Examples of thermal initiators (f2) suitable for free radical polymerization include peroxide compounds such as peroxy(di)esters, hydroperoxides, (di)alkyl peroxides, ketone peroxides, peroxyketals, peroxyacids, peroxydicarbonates, peroxymonocarbonates and benzopinacol.
[0137] Examples of suitable peroxyesters include cumyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, t-amyl peroxyneodecanoate, t-butyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxypivalate, t-amyl peroxypivalate, t-butyl peroxypivalate, didecanoyl peroxide, dilauroyl peroxide, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)-hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, dibenzoyl peroxide, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxyisobutyrate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxyacetate, and t-butyl peroxybenzoate.
[0138] Examples of suitable hydroperoxides include di-isopropylbenzene monohydroperoxide, terpane hydroperoxide, cumene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, tert-butyl hydroperoxide, and tert-amyl hydroperoxide.
[0139] Examples of suitable alkyl peroxides include diisobutyryl peroxide, di-(3,5,5-trimethylhexanoyl)-peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di-(tert-butylperoxy)cyclohexane, 2,2-di-(tert-butylperoxy)-butane, di-tert-amyl peroxide, diisopropyl peroxide, di-(2-tert-butyl-peroxyisopropyl)-benzene, 2,5-dimethyl-2,5-di-(tert-butylperoxy)-hexane, tert-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and di-tert-butyl peroxide.
[0140] Examples of suitable peroxydicarbonates include di-(4-tert-butylcyclohexyl)peroxydicarbonate, di-(2-ethylhexyl)peroxydicarbonate, di-n-butylperoxydicarbonate, dicetyl peroxydicarbonate, dicetyl peroxydicarbonate, and mixtures thereof.
[0141] Examples of suitable peroxymonocarbonates include tert-amyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxyisopropyl carbonate, and tert-butyl peroxy-2-ethylhexyl carbonate.
[0142] In the composition of the present invention, the peroxide compound (f2) is preferably present in a proportion of 0 wt % to 10 wt %, more preferably 0.1 wt % to 5 wt %, based on the total weight of the composition.
[0143] In addition to the free-radical photoinitiator (f1), a thermal initiator (f2) may also be present or may be used instead of the free-radical photoinitiator (f1).
[0144] Component (g): Additive
[0145] In addition to components (a) to (f), the composition of the present invention may further comprise other additives (g). Preferably, the additive (g) comprises a toughness improver, such as core-shell particles (Kaneka KaneAce TM Series, Dow Paraloid TM EXL series, Wacker ) or block copolymers, reactive elasticizers (for example blocked isocyanate prepolymers according to US Pat. No. 5,278,257 A), dyes, pigments, fluorescent agents, thixotropic agents, thickeners, stabilizers, antioxidants, plasticizers, fillers, flame retardants, corrosion inhibitors, inert diluents, catalysts, leveling and wetting additives and adhesion promoters, and combinations thereof.
[0146] In addition to the polymer filler (d), other organic or inorganic fillers may be included as additives (g1) in component (d). This allows, for example, the mechanical, enthalpy, thermal, rheological and electrical properties of the composition to be adjusted and can be used advantageously to increase the resistance of the cured composition to temperature, humidity and media influences.
[0147] Suitable fillers (g1) are, for example, compounds from the group consisting of oxides, nitrides, borides, carbides, sulfides and silicides of metals and semimetals (including mixed compounds of multiple metals and / or semimetals); carbon modifications (such as diamond, graphite and carbon nanotubes); silicates and borates of metals and semimetals; various types of glasses; metals and semimetals in elemental form; metals and semimetals in the form of alloys or intermetallic phases; and particles of polymer compositions (such as silicone resins and polytetrafluoroethylene (PTFE)).
[0148] As described in EP 3 943 534 A1, IR-absorbing dyes can advantageously be used as additives (g2) to accelerate the heat input for the re-detachment of the composition, in particular when irradiated by an IR emitter. This not only enables more efficient heat input to the adhesive layer, but also rapid heating, and thus faster re-removal of the cured composition.
[0149] In the composition of the present invention, the proportion of other additives (g) is 0 wt % to 50 wt %, preferably 1 wt % to 30 wt %, based on the total weight of the composition.
[0150] The formulation of the composition according to the invention:
[0151] According to a preferred embodiment, the composition according to the invention consists of the following components:
[0152] a) at least one epoxy compound, the epoxy compound comprising at least one difunctional or polyfunctional aromatic epoxy compound;
[0153] b) at least one solid nitrogen-based curing agent selected from the group of amines, hydrazides, cyanamides or imidazoles;
[0154] c) optional accelerator for epoxy curing;
[0155] d) 15 wt% to 50 wt% of an organic filler selected from the group of polyamides;
[0156] g) Optional other additives.
[0157] According to a second preferred embodiment, the composition according to the invention consists of the following components, based on the total weight of components a) to g):
[0158] a) at least one epoxy compound, the epoxy compound comprising at least one difunctional or polyfunctional aromatic epoxy compound;
[0159] b) at least one solid nitrogen-based curing agent selected from the group of amines, hydrazides, cyanamides or imidazoles;
[0160] c) optional accelerator for epoxy curing;
[0161] d) 15 wt% to 50 wt% of an organic filler selected from the group of polyamides;
[0162] e) 1 wt% to 30 wt% of a compound curable by free radical polymerization, the compound comprising at least one (meth)acrylate;
[0163] f) at least one initiator for free radical polymerization, said initiator being selected from the group of photoinitiators and / or thermal initiators; and
[0164] g) Optional other additives.
[0165] In the case where the composition according to the second embodiment comprises at least one photoinitiator for free radical polymerization, it can also be solidified by irradiation. Therefore, they are suitable for converting the liquid composition into a morphologically stable state before thermal curing, so that it no longer flows. This facilitates the handling of the composition in subsequent process steps. It is also possible to use a thermal initiator as component (f) instead of the use of a photoinitiator or together with the use of a photoinitiator as component (f). In these ways, the free radical curable component can be completely cured by heating even in shadowed areas.
[0166] Curing of the composition according to the invention
[0167] At a temperature of 100° C. to 160° C., the composition can be completely cured within 4 hours, preferably within 2 hours.
[0168] Stepped temperature curing profiles are also within the meaning of the present invention.
[0169] The composition may be cured by heating, for example, in a convection oven, by a thermode, an IR radiator, laser, microwaves, or induction.
[0170] If the composition according to the invention is formulated as two-component or multi-component, curing can take place at room temperature over a period of up to 7 days, preferably up to 5 days.
[0171] The curing temperature of the composition according to the invention is preferably selected to be below the melting point of component (d). This makes it possible to avoid melting of the semicrystalline polymer filler (d) during curing.
[0172] The heat of fusion of the cured composition as determined by DSC measurement is preferably at least 10 J / g, more preferably at least 20 J / g.
[0173] Use of the composition according to the invention
[0174] Compositions according to the present invention are suitable for producing re-detachable adhesives, coatings and castings. In particular, the composition is suitable for parts that are exposed to high mechanical and thermal loads for a long time or periodically in normal operation. The cured composition is characterized by its high strength and durability, and can be re-detached at a higher temperature. The parts joined using the composition can be separated again with very little external force by being heated to a predetermined temperature. Preferably, the removal temperature is located at or above another inflection point of the DMTA curve of the storage modulus of the cured composition.
[0175] For example, the composition can be used to produce electric motors (E-motors). In particular, the composition can be used to bond magnets in electric motors. In particular, magnets in high-performance electric motors contain rare earth metals, the recovery of which is generally of high economic value. At the same time, during the service life of the electric motor, the composition is exposed to high temperatures and, depending on the application, sometimes to loads from the medium (such as dust, oil, grease, coolants, lubricants or solvents). The composition according to the invention can also withstand these loads during long-term operation.
[0176] Other applications in which the compositions of the invention can be used advantageously include structural bonding in the field of powertrain systems in automotive applications, and also bonding or casting applications, for example in the chip industry.
[0177] In principle, the compositions described are always suitable for applications using very expensive components, the disposal of which represents a huge economic loss.
[0178] If the cured composition is to be removed from the component or substrate composite, the removal temperature is advantageously chosen to be at or above the further inflection point of the DMTA curve of the storage modulus of the cured composition.
[0179] Preferably, the removal temperature is in the range between the further inflection point temperature and at most 50° C., more preferably at most 20° C., above the end point temperature of the modulus drop. In a preferred embodiment, the removal temperature is at most 320° C., more preferably at most 280° C., particularly preferably at most 250° C. At higher temperatures, there is a risk that the parts to be separated may be thermally damaged.
[0180] The heat required to reach the removal temperature can be introduced by, for example, an oven, induction, laser, microwave, thermode, or infrared radiator.
[0181] The duration of the heat input varies depending on the manner in which the heat is generated, the size and nature of the parts, the amount of composition to be separated, and the accessibility of the adhesive layer to the heat.
[0182] In particular, for large components made of metallic materials, heat input can be achieved quickly and efficiently via an alternating induction field.
[0183] Above the temperature of the further inflection point of the DMTA curve of the storage modulus, the joints from the cured composition can be separated by small mechanical forces and the parts can be separated from each other. Even in the case of heating above the removal temperature, the low residual strength of the cured composition ensures that in particular large parts will not be separated from each other in an uncontrolled manner.
[0184] It would be advantageous if the storage modulus of the cured composition is as low as possible, so that the necessary force input applied to the components can be kept low. However, this conflicts with the requirement for a strong and durable bond even under high thermal and mechanical loads. In order to meet both requirements, the storage modulus of the cured composition in the DMTA curve between the start and the end of the temperature range including the further inflection point above the glass transition temperature preferably drops by at least 30%, more preferably by at least 45%.
[0185] A smaller drop in the storage modulus may also be caused by a temperature-related softening of the cured composition. However, this drop is essentially continuous over a wide temperature range and does not represent an inflection point in the sense of the present invention. Only by using polymer fillers (d) is it possible to achieve effective thermomechanical removability to a sufficient extent.
[0186] At temperatures below the further inflection point, the joined parts made using the composition of the invention exhibit high strength (particularly tensile shear strength) and high tolerance to mechanical, thermal and chemical loads. Only at temperatures exceeding the further inflection point and / or when the removal temperature is reached, an almost abrupt strength drop occurs.
[0187] Joining method or coating method using the composition according to the present invention
[0188] The method for manufacturing a component using the curable composition according to the present invention preferably comprises the following steps:
[0189] a) applying the composition to a first substrate in a quantitative manner;
[0190] b) optionally, providing a second substrate to form a substrate composite, wherein the second substrate is contacted with the composition;
[0191] c) optionally, irradiating the composition with actinic radiation to achieve a sufficient anchor strength for further processing of the first substrate or substrate composite; and
[0192] d) heating the optionally irradiated composition on the substrate or substrate composite to a predetermined curing temperature until cured, thereby forming a component having a substrate and a cured adhesive layer,
[0193] The adhesive layer is connected to the substrate and optionally to a further substrate, wherein the adhesive layer can be thermomechanically separated from the substrate by heating to a predetermined removal temperature.
[0194] In order to ensure sufficient application feasibility, preferably, the composition is liquid at room temperature and generally has a viscosity of 10 Pa·s to 700 Pa·s.
[0195] If the application requires, optionally after joining in step b), the first substrate or the second substrate can be aligned relative to each other before the composition is cured by irradiation.
[0196] In another preferred embodiment, the composition is used in a so-called B-stage process. Here, the metered application of the composition to a first substrate and the provision of a second substrate can be separated in time and space, wherein the composition is solidified by actinic radiation after application to the first substrate. The solidification step limits the fluidity to such an extent that no further changes in the applied pattern on the component occur. In a subsequent step, the substrate can be joined to another substrate and subsequently fully cured by heating.
[0197] The composition suitable for the method can be obtained by the second preferred embodiment.
[0198] Properties of the Cured Compositions
[0199] Cured compositions based on aromatic epoxy compounds are not only removable from the substrates to which they are bonded, coated or cast, but also have a high resistance to media, temperature and humidity. At the same time, they also exhibit high bond strengths under temperature loads.
[0200] The cured composition has a tensile shear strength on metals such as aluminum or steel of at least 5 MPa at room temperature and at least 3 MPa at the operating temperatures present in the application.
[0201] Preferably, the cured composition has an elastic modulus greater than 100 MPa, preferably greater than 150 MPa.
[0202] Preferably, the glass transition temperature of the cured composition is at least 80° C., preferably at least 100° C., particularly preferably at least 120° C. A high glass transition temperature ensures a low drop in strength even at high temperatures.
[0203] According to the present invention, the cured composition is removable at a predetermined removal temperature, preferably at or above the temperature of the other inflection point of the storage modulus DMTA curve. At the removal temperature, the tensile shear strength of the cured composition on steel is preferably at most 2 MPa, more preferably at most 1 MPa.
[0204] The at least partially crystalline polyamide used as filler (d) has a relatively narrow melting range. Therefore, once the starting point of the modulus drop in the storage modulus DMTA curve is exceeded, a drop in the strength of the cured composition occurs within a narrow, limited temperature interval. Therefore, the removal temperature of the composition can be reliably adjusted and adapted to the respective application by selecting the filler (d).
[0205] In the curve of dynamic mechanical thermal analysis (DMTA), the storage modulus of the cured composition measured according to temperature has at least one other inflection point higher than the glass transition temperature. The inflection point is located in the temperature range in which both the storage modulus and the strength of the cured composition show a sharp and significant decrease.
[0206] Thus, in addition to the stage occurring at the glass transition temperature, the addition of the at least partially crystalline polyamide also produces another stage in the storage modulus of the cured composition. When heated to a temperature exceeding the further inflection point, this stage is broken through and the storage modulus of the composition used in the present invention decreases significantly. In particular, the storage modulus between the start and end of the temperature range including the further inflection point decreases by at least 30%, more preferably at least 45%.
[0207] In a similar temperature range, the tensile shear strength of the steel-steel bond of the composition used in the invention is also reduced, so that at temperatures above the further inflection point, the force required to remove the adhesive layer is significantly reduced. At the same time, the at least partially crystalline polyamide as filler (d) does not have a negative impact on the glass transition temperature and the tensile shear strength at room temperature of the cured composition.
[0208] Measurement methods and definitions used
[0209] Irradiation
[0210] For irradiation, a DELOLUX 20 / 365 LED lamp from DELO Industrie Klebstoffe GmbH & Co. KGaA was used at a wavelength of 365 nm and an intensity of 200 ± 20 mW / cm 2 The composition according to the invention was irradiated for 60 seconds.
[0211] Curing
[0212] "Crosslinking" or "curing" is defined as polymerization or addition beyond the gel point. The gel point is the point at which the storage modulus G' equals the loss modulus G" in oscillatory rheological measurements. The composition was cured in a convection oven at 150°C for 40 minutes.
[0213] Room temperature
[0214] Room temperature is defined as 23±2°C.
[0215] Evaluation of light curing
[0216] To evaluate photocoagulation (solid vs. liquid), the compositions were evaluated optically. Optionally, a tactile test can be performed using a plastic spatula.
[0217] Viscosity measurement
[0218] The viscosity was determined with a Rheometer Physica MCR302 rheometer from Anton Paar at 23° C. using a standardized PP20 measuring cone with a gap of 500 μm at a shear rate of 10 / s.
[0219] Determination of melting point and heat of fusion
[0220] According to DIN EN ISO 11357-3:2018-07, the heat of fusion and the melting point are determined using differential scanning calorimetry (DSC) on a "DSC2" from Mettler Toledo. The melting point is defined as the temperature at the maximum of the maximum endothermic peak in the corresponding measurement run. An Al crucible with a perforated lid of 40 μL was used. The measurement of the semi-crystalline polymer filler (d) was carried out in a range of 30°C to 280°C under nitrogen at a heating rate of 10K / min. Unlike the standard, the melting point and the heat of fusion are determined in the first heating run. In order to measure the melting point and the heat of fusion of the cured composition, it is first cured in a convection oven at 150°C for 40 minutes. Optionally, irradiation is performed in advance. Using an Al crucible with a perforated lid of 40 μL, measurements are performed in air at a heating rate of 10K / min in a temperature range of 0°C to 250°C.
[0221] Tensile shear strength at room temperature (aluminum test sample)
[0222] The tensile shear strength at room temperature was determined in accordance with DIN EN ISO 1465:2009-07. Test specimens with the dimensions of 100 mm long, 25 mm wide and 1.6 mm thick were used and the bonding was carried out with an overlap of 12.5 mm and an adhesive layer thickness of 0.1 mm. The test speed was 10 mm / min. The tests were carried out at room temperature on an "AllroundLine 20 kN" universal testing machine from Zwick Roell. The curing time was 40 minutes at 150 ° C, plus the heating time. As test specimens, AlMgCu test specimens with aluminum plating and corundum blasting were used.
[0223] Determination of tensile shear strength at elevated temperatures (steel test specimens)
[0224] The tensile shear strength at elevated temperatures (temperature resistance) is determined in accordance with DIN EN 14869-2:2004-10. The length of the test specimens differs from the standard, with the long side being 50 mm instead of 57.5 mm and the short side being 30 mm instead of 51 mm. The test specimen thickness is 15 mm instead of 12 mm. The overlap length of the bond is 10 mm. The thickness of the adhesive layer is 0.3 mm. The test speed is 10 mm / min at the respectively specified test temperature. The tests are carried out on an "AllRoundLine" testing machine from Zwick Roell at the specified temperature. The curing time is 40 minutes at 160°C, plus a heating time of 45 minutes. The test specimens consist of corundum-blasted steel (S235).
[0225] Determination of glass transition temperature (TG) and storage modulus
[0226] The dynamic mechanical properties of the cured compositions were determined by dynamic mechanical thermal analysis (DMTA) according to ISO 6721. Dimensions 40x5x0.5 mm 3 The test sample is cured at 150°C for 40 minutes in a suitable plastic mold. The glass transition temperature is defined as the temperature at which the first derivative value of the storage modulus (E') is maximum (inflection point, see ISO 6721-11:2012 Section 3.1). The storage modulus at each temperature is determined according to ISO 6721-4:2008. The measurement is carried out in a temperature range of 0-300°C, with a heating rate of 1K / min, a frequency of 1Hz and an amplitude of 30μm. "DMA 242E" from Netzsch is used as a measuring device.
[0227] Particle size distribution
[0228] The particle size distribution is determined by laser diffraction using a S3500 particle size analyzer from Microtrac according to ISO 13320. The distribution expressed as particle size D50 corresponds to the median volume particle size.
[0229] Preparation of curable compositions
[0230] To prepare the curable compositions used in the following examples, the liquid ingredients were first mixed, and then fillers and optionally other solids were added by means of a laboratory stirrer, laboratory dissolver or speed mixer (Hauschild) until a homogeneous composition was formed. Compositions containing photoinitiators and sensitive to visible light must therefore be prepared under light other than the excitation wavelength of the photoinitiator or sensitizer.
[0231] All compounds used to make the curable compositions are listed below along with their abbreviations.
[0232] Component (a): Epoxy compound
[0233] (a1) Epikote Resin 169 (a mixture of bisphenol A diglycidyl ether and bisphenol F diglycidyl ether; available from Westlake Corporation);
[0234] (a2) Kane ACE MX 257 (rubber particles dispersed in bisphenol A diglycidyl ether; available from Kaneka Corporation);
[0235] (a3) Tactix 742 (triglycidyl ether of tris(hydroxyphenyl)methane; available from Huntsman Corporation);
[0236] (a4) Epilox P 13-21 (1,4-butanediol diglycidyl ether; available from Leuna Harze);
[0237] (a5) Epikote Resin 828LVEL (low-chlorinated bisphenol A resin; available from Westlake Corporation);
[0238] Component (b): Nitrogen-based curing agent
[0239] (b1) Epikure Curing Agent 921 Super SH (dicyandiamide; available from Westlake Corporation);
[0240] (b2) Ancamine 2014FG (amine-based solid curing agent; available from Evonik);
[0241] (b3) Technicure IDH-J (isophthalic acid dihydrazide; available from ACCI Specialty Materials);
[0242] (b4) Adeka Hardener EH-5011S (imidazole-based solid curing agent; available from Adeka Corporation)
[0243] Component (c): Accelerator
[0244] (c1): DYHARD UR 500 (Uron-based accelerator, available from Alzchem)
[0245] Component (d): filler
[0246] (d1): Orgasol 1002D NAT 1 (polyamide 6; available from Arkema), DSC melting range (10 K / min) from 205°C (starting point) over 214°C (peak) to 220°C (end point), enthalpy 116 J / g.
[0247] (d2): Rilsan PA11 D30 NAT (polyamide 11; available from Arkema), DSC melting range (10 K / min) from 180°C (starting point) over 190°C (peak) to 194°C (end point), enthalpy value 85 J / g.
[0248] Component (e): Free radical curable compound
[0249] (e1): Photomer 4006 (trimethylolpropane triacrylate; available from IGM Resins)
[0250] Component (f): Initiator for free radical polymerization
[0251] (f1): Genocure TPO-L (photoinitiator; available from Rahn AG)
[0252] Component (g): Other additives
[0253] (g1): Cab-O-Sil TS-720 (rheological additive; available from Cabot Corporation)
[0254] (g2): Ulmer WeiβXMF (micronized chalk filler; available from Eduard Merkle GmbH & CO. KG)
[0255] (g3): Elvacite 2614 (micronized methacrylate copolymer; available from Mitsubishi Chemical Corporation)
[0256] (g4): Dynasylan GLYMO (adhesion promoter; available from Evonik)
[0257] The composition of the curable composition produced in this way and the properties measured for the composition are given in the table below.
[0258] Table 1: Composition of curable composition
[0259]
[0260]
[0261]
[0262] Example V1 and Example V2 according to the invention contain a semi-crystalline polyamide with a melting point of 214°C (defined as the peak temperature of the DSC measurement) as filler (d). The addition of the semi-crystalline polymer produces a further step in the DMTA curve of the storage modulus of the composite, which step has another inflection point above the glass transition temperature. In the case of Example V1 and Example V2, the further inflection point is 190°C and 195°C, respectively. When the composition is heated beyond the further inflection point, this stage is crossed. In Example V1 and Example V2 according to the invention, the storage modulus decreases by 49% and 69%, respectively, in the temperature range between the start and end of the modulus decrease.
[0263] Comparative Example C1 does not contain a polymer filler. The DMTA curve of the storage modulus of Comparative Example C1 does not have a further inflection point above the glass transition temperature. Composition C1 is therefore not suitable for the production of thermomechanically removable joints in the sense of the present invention.
[0264] In the temperature range of 180°C to 220°C, the tensile shear strength of the steel-steel bond with the composition V2 according to the invention decreased by 68%, while the tensile shear strength of the composition of comparative C1 decreased by only 29%. The high temperature strength of V2 at 180°C is 3.7 MPa, while at 220°C, its temperature strength is only 1.17 MPa. Therefore, the temperature strength of the composition of Example V2 at 220°C is 4.8 times lower than that of comparative example C1. Therefore, the force required for the joint made with the composition of Example V2 during the thermomechanical removal process is much smaller than that of the joint made with the composition of comparative example C1. In addition, the polymer filler (d) does not have a negative effect on the glass transition temperature and the tensile shear strength at room temperature of the cured compound. Therefore, the compound according to the invention is able to withstand thermal and mechanical loads.
[0265] The composition in comparative example C2 contains an amorphous polymer as filler. The use of an amorphous filler (g3) instead of a semi-crystalline polymer filler (d) does not lead to a further decrease in the storage modulus. In the DMTA measurement, there is no further inflection point above the glass transition temperature. In addition, there is no difference in the temperature resistance strength at 180°C and 220°C. Therefore, composition C2 is also not removable in a thermomechanical manner in the sense of the present invention.
[0266] The composition of Example V3 has a different epoxy resin composition than Example V2. The cured composition of Example V3 also shows another inflection point above the glass transition temperature and an 81% drop in the storage modulus in the temperature range between the start and end points, so that, like the compositions of Examples V1 and V2, this composition can be efficiently removable thermomechanically.
[0267] According to a second preferred embodiment, the composition of Example V4 is a dual-curing type. Example V4 also contains (meth)acrylate as a free radical curable compound (e) and a photoinitiator (f1) for free radical polymerization. The composition can be solidified by irradiation with actinic radiation and then cured in a warm state. Due to the use of a semi-crystalline polymer filler (d), the storage modulus of the composition in the DMTA curve also presents another inflection point above the glass transition temperature of the cured compound. In the temperature range between the starting point and the end point, the storage modulus decreases by 59%. This means that the composition of Example V4 can also be effectively removed by thermomechanical means.
[0268] The compositions of Example V5 and Example V7 according to the invention and the composition of Comparative Example C3 contain a combination of multiple hardeners (b) for epoxy curing. By combining multiple hardeners, rapid curing can be achieved at low temperatures without the additional addition of accelerators (c). The cured composition of Example V5 shows another inflection point above the glass transition temperature in the temperature range between the starting point and the end point, and the storage modulus decreases by 69%. This means that the composition of Example V5 can also be effectively removed by thermomechanical means.
[0269] The compositions of Example V6 and Example V7 according to the present invention contain a semi-crystalline polyamide having a melting point of 190° C. as a polymer filler (d2). In the DMTA measurement, the storage modulus decreases in the temperature range of 172° C. to 180° C., with another inflection point appearing at 174° C. Therefore, the cured composition can be effectively removed again at a temperature below 190° C.
[0270] In contrast, the composition of Comparative Example C3 does not show a significant decrease in storage modulus above the glass transition temperature in the DTMA measurement.
[0271] Figure 1 The DMTA curves of the storage modulus of the cured compositions of Example V5 and Example V7 are shown. The glass transition temperature of the resin matrix shows inflection points at 117°C and 124°C, respectively. Each curve also has another inflection point above the glass transition temperature. For Example V5, the other inflection point is 199°C, and for Example V7, the other inflection point is 174°C. Therefore, the first-order derivative of the storage modulus reaches a maximum value at the glass transition point and also reaches a maximum value at another inflection point in the modulus drop region. In the temperature range between the starting point and the end point, the storage modulus of Composition V5 and Composition V7 decreased by 69% and 76%, respectively.
[0272] The DMTA curve of Comparative Example C3 is also as follows Figure 1 As shown, there is no further inflection point above the glass transition temperature of the resin matrix of 120° C. Only a slight drop in the storage modulus is observed, which is due to the temperature-related softening of the composition. Therefore, the composition is not removable in the sense of the present invention.
Claims
1. Use of a curable composition for producing a component having a thermomechanically removable joint, coating or casting, wherein: The composition comprises the following components: (a) at least one epoxy compound, the epoxy compound comprising at least one difunctional or higher functional aromatic epoxide; (b) at least one curing agent suitable for epoxy curing; (c) optionally an accelerator for epoxy curing; (d) at least one polymer filler, the proportion of the polymer filler being 15 wt% or more based on the total weight of the composition, the polymer filler being selected from the group of polyamides; (e) optionally one or more compounds curable by free radical polymerization; (f) optionally at least one initiator for free radical polymerization; and (g) optionally other additives, wherein the polymer filler is present in the composition as an at least partially crystalline solid and has a melting point of at least 120°C.
2. The use according to claim 1, characterized in that The proportion of the polymer filler is at least 20 wt%.
3. The use according to claim 1 or 2, characterized in that The melting point of the filler is in the range of 120°C to 300°C.
4. Use according to any one of the preceding claims, characterized in that The filler has a heat of fusion of at least 40 J / g.
5. Use according to any one of the preceding claims, characterized in that The filler has a particle size distribution with a median particle size D50 of at most 100 μm.
6. Use according to any one of the preceding claims, characterized in that The cured composition has at least one other inflection point higher than the glass transition temperature in the DMTA curve of the storage modulus.
7. Use according to any one of the preceding claims, characterized in that The components are magnets, stators and / or rotors for electric motors.
8. A curable composition for producing a thermomechanically removable joint, coating or casting, wherein: The composition comprises the following components: (a) at least one epoxy compound, the epoxy compound comprising at least one difunctional or higher functional aromatic epoxide; (b) at least one nitrogen-based curing agent suitable for epoxy curing; (c) optionally an accelerator for epoxy curing; (d) at least one polymer filler, the proportion of the polymer filler is 20 wt% or more based on the total weight of the composition, the polymer filler is selected from the group of polyamides; (e) optionally one or more free radical radiation curable compounds; (f) optionally at least one initiator for free radical polymerization; and (g) optionally other additives, wherein the polymer filler is present in the composition as an at least partially crystalline solid, the heat of fusion of the polymer filler is above 40 J / g, and wherein the melting point of the polymer filler is at least 120°C.
9. A method for manufacturing a part using the curable composition according to any one of claims 1 to 8, wherein the method comprises the following steps: applying the composition to a first substrate in a quantitative manner; optionally providing another substrate to form a substrate composite, wherein the other substrate is contacted with the composition; Optionally, irradiating the composition with actinic radiation, wherein the irradiated composition achieves a sufficient anchor strength for further processing of the first substrate or substrate composite; and The optionally irradiated composition on the substrate or substrate composite is heated to a predetermined curing temperature until cured, thereby forming a component having a substrate and a cured bonding layer connected to the first substrate and optionally to the further substrate, wherein the bonding layer can be thermomechanically separated from the substrate by heating to a predetermined removal temperature.
10. A component obtainable by the method according to claim 9.
Citation Information
Patent Citations
Hardenable two-component compound
DE102018121067A1
Method of producing recycled raw material powder for use in bonded magnet and method of recycling bonded magnet
EP1096517A2
Composite materials with improved performance
EP2084205B1
Mercaptoalkyl glycolurils and use of same
EP3075736A1
Use of red to near-infrared heat-generating organic dyes for reprocessing / recycling polymers
EP3943534A1